PEMDAMPINGAN UMKM (USAHA MIKRO KECIL MENENGAH) DALAM CUSTOMER RETENTION MARKETING PRODUK OYEK DI DESA SUKAMULIA - Firdanianty, Firdanianty; Herfriady, Herfriady (Lembaga Penelitian dan Pengabdian Masyarakat STISIPOL Candradimuka Palembang, 2021)
Empowerment of MSMEs (Small and Medium Micro Enterprises) Through the Program of mothers in sports villages. This assistance examines how the Empowerment of MSMEs (Small and Medium Micro Enterprises) in customer retention marketing of oyek products in sukamulia village. Thembuatan of oyek products is carried out assistance with mothers. Meanwhile, oyek products are processed products produced by housewives. In this assistance, it is expected to have an impact and improve the economy of mothers in marketing oyek products. to describe or explain about oyek products, namely empowering MSMEs (Small and Medium Micro Enterprises) through the Program to Build a Prosperous Family Economy in Sukamulia Village of Banyuasin Regency. Based on the results of the assistance, it was found that the Empowerment of MSMEs (Small and Medium Micro Enterprises) through the Program to Foster a Prosperous Family Economy in sukamulia was found in the field that has been disclosed by the community, especially pre-welfare mothers in Sukamulia Village, satisfied with the mentoring program that took place about 3 months ago in April. 2020. Mentoring program is considered able to provide business and capital assistance to them or MSME actors, especially pre-welfare mothers in marketing oyek products.The existence of oyek product management assistance proved to get a place in the hearts of the community, because the community felt that this mentoring program brought good effects and could be felt by every individual who participated in its development through the mentoring program, because until the end of April 2021 there were already 85 more oyek product outlets managed by pre-country mothers after the end of April 2021. Follow the development of oyek products by using customer retention marketing strategies.